Correlation of triglyceride glucose-body mass index, triglyceride glucose/high-density lipoprotein cholesterol ratio, and triglyceride glucose index with blood sugar and hemoglobin A1C in patients with type 2 diabetes mellitus: A cross-sectional study - Akula, Srikanth; Akkina, Swetha; Gandham , Rajeev; Batakala, Preethi; Atla, Bhagyalakshmi; Uha Priya, Sunkara; Bonthu, Divija Reddy (Asian Journal of Medical Sciences, 2025)
Background: Type 2 diabetes mellitus (T2DM) is one of the most common endocrine diseases characterized by increased blood glucose. Uncontrolled diabetes is associated with the development of micro- and macrovascular complications. Aims and Objectives: This study aimed to assess and correlate triglyceride glucose-Body mass index (TyG-BMI) index, triglycerides (TG)/high-density lipoprotein cholesterol (HDL-C) ratio and TyG index with blood sugar and hemoglobin A1C (HbA1c) in patients with T2DM. Materials and Methods: This current study was a cross-sectional study where 252 subjects, were recruited and they were categorized into 126 diabetic and 126 nondiabetic subjects. All parameters and anthropometric measurements were done following standard guidelines. Results: In this study, a significant increase in mean age (56.3±10.3 years), BMI (25.0±2.4 kg/m2), and, systolic blood pressure (120.0±7.6 mmHg) were observed in T2DM subjects compared to nondiabetic subjects. Concerned with biochemical parameters, significant increase in fasting blood sugar (FBS), postprandial blood sugar, HbA1c, urea, creatinine, total cholesterol, triglycerides (TG), LDL-C, very low-density lipoprotein-cholesterol and non-HDL-C were observed in T2DM subjects compared to nondiabetic subjects. Conclusion: The present study may conclude that there is a significant increase in TyG-BMI index, TG/HDL-C, and TyG index in T2DM patients and their positive correlation with FBS and HbA1c. The measurement of these markers will provide better information on IR status.